The Social skills in bullying of 5th year high school students from the educational institution "República de Bolivia" Villa el Salvador, Lima 2016 - Holguín Quiroz, Lidia (2022)
The scientific research we have done is basic, it is quasi experimental, the study factors are two: social skills and bullying in high school students, of 5to secondary, the educational institution "Republic de Bolivia" Villa El Salvador, Lima 2016. The population is confirmed by 240 students the institution under study is made up of 60 students control group and 60 experimental group, which represent a 120 students. The research design is transactional, quasi experimental, bivariate, transversal. For data collection, there will be 20 workshops on Social Skills and a questionnaire about the Bullying that will be applied at the beginning and then at the end of the workshop to see the difference between the control group and the experimental group. The instruments fulfill validity and reliability. The study poses the following research hypothesis: There is a significant difference between control group and the experimental group in the post test, after applying the Thaso   workshop on Social Skills and  Bullying. The results obtained allow us to reject the alternative hypothesis and accept the hypothesis investigated, since we find that in the control group the p-value is not less than 0.05, therefore there is no significant difference and in the experimental group p - value with a level of significance of 95% is 0.00 of reliability according to the non-parametric Mann-Whitney U test, therefore we accept the hypothesis investigated: There is a significant difference between the control group And the experimental group in the post test, of our study.